3D geometric modeling of three-thread fleece fabric based on micro-CT. Issue 9 (May 2023) - Yu, Yuelin; Wu, Weili; Chen, Weilai; Shao, Yiqin; Zhu, Chunhong; Gu, Xuefeng; Hu, Shengchao
In the era of information technology, the update cycle of textiles is shortened, which urgently demands new design and higher quality. Therefore, the traditional mode of quality control after knitting faces great challenges due to the hysteresis and huge material loss. This problem can be solved by the digitization of textiles, which aims at adjusting before knitting, while a key step of digitization is geometric modeling. Herein, a three-dimensional geometric model of three-thread fleece fabric is constructed for the first time based on micro-computed tomography technology. First, the computed tomography scan data were flipped, clipped and rendered by software DragonFly Pro to observe the loop structure more clearly, annotated and probed to obtain the coordinate points of yarn center trajectory. According to those coordinate points, the spatial trajectory of each yarn was reconstructed by the spline curve method using software Catia, then the unit cell models of each group of yarns were obtained and assembled to form a complete three-dimensional loop model. Finally, the constructed geometric model was compared with the actual fabric, and standard curve equations of the loop trajectory were fitted. The meso-scale model of three-thread fleece fabric was established accurately which clearly reflected the relationship of geometry position between yarns, providing a precise geometric model for further study on the simulation and performance prediction of knitted fabrics in future work.